Reservoir operation for recession agriculture in Mekong basin, Laos - Reis, J.; Culver, T.B.; Lacombe, Guillaume; Senaratna Sellamuttu, Sonali (American Society of Civil Engineers, 2015)
As hydropower dam construction in rapidly growing economies dislodges communities, rural development experts must help the displaced make their livelihoods in new lacustrine environments. One question is whether the dam infrastructure can directly benefit those who remain within the vicinity of the reservoir. Integrated water resource management seeks to concurrently consider hydrological, socioeconomic, and ecological factors, yet water managers lack the information needed to include livelihoods in their analyses. The objective of this paper is to develop tools and plans for coordinating hydropower reservoir operation and management for rural livelihoods. Specifically, this study investigates how dam management may accommodate vegetable farming on the banks of a reservoir. The intervention investigated is to lower water levels during the cultivation period in order to expose shoreline gardens. Based on the recession agriculture rule, evaluated through simulation of a dam in Lao People’s Democratic Republic, the average annual hydropower production was reduced by between 0.4 and 8.1%, depending on the agricultural goal, with the loss to power occurring mainly in the months April to June. By focusing on hydropower reservoir systems, the techniques developed in this study have the potential to be applied to support communities throughout the world that farm on the shorelines of water reservoirs.